Implementasi Ekonomi Sirkular pada Pengelolaan Limbah Produksi Ikan Keumamah di Desa Deah Raya sebagai Perwujudan Green Chemistry - Puspita, Kana; Izzaty, Nur; Agustina, Sri; Fadlia, Faradilla; Ansari, Marzuki (Penerbit Widina, Widina Media Utama, 2025)
Deah Raya is a coastal village rich in marine potential, particularly with the abundance of skipjack and tuna as the main raw material for the production of wooden fish or commonly referred to as keumamah. Several issues leading to insufficiently satisfying production process of keumamah including the fact that the villagers managed the business individually and the product was not well packaged. In addition, the waste from fish processing results in complaints from the neighbouring community. The aim of this services is knowledge and skill transfer related to the implementation of the economy circular as an alternative to overcome these problems. The results of this service activity are that two production groups have been formed from a total of 20 female participants who represent four hamlets in Deah Raya Village. The service team also provided education and conducted workshops related to the concepts of circular economy and how to manage waste from fish processing. After the workshop, the production groups managed the supply of raw materials to become more stable, mitigated production risks, and packaged the product in order to extend the product shelf life. They also started to process the waste into compost and are expected to sustain the efforts until it has commercial value and at the same time reduce the adverse impact on the environment.ABSTRAKDesa Deah Raya merupakan desa pesisir yang kaya akan potensi laut, terutama dengan melimpahnya ikan cakalang dan ikan tongkol sebagai bahan baku utama produksi ikan kayu atau yang lazim disebut dengan keumamah. Beberapa kendala yang menyebabkan kurang maksimalnya pengolahan ikan keumamah di antaranya karena penduduk masih mengelola usaha ini secara individu dan belum terkemas dengan baik. Selain itu, limbah dari hasil pengolahan ikan menimbulkan keluhan dari masyarakat sekitar. Tujuan dari pengabdian ini adalah transfer pengetahuan dan keterampilan terkait dengan penerapan ekonomi sirkular sebagai alternatif untuk mengatasi masalah tersebut. Hasil dari kegiatan pengabdian ini yaitu telah terbentuk dua kelompok produksi dari total 20 ibu-ibu peserta tetap kegiatan yang mewakili empat dusun di Desa Deah Raya. Tim pengabdi juga memberikan edukasi dan workshop terkait dengan konsep ekonomi sirkular dan cara pengelolaan limbah hasil dari pengolahan ikan. Setelah workshop, kelompok produksi mengelola pasokan bahan baku sehingga menjadi lebih stabil, memitigasi risiko produksi, serta melakukan pengemasan produk sehingga dapat memperpanjang masa simpan ikan keumamah yang akan dijual. Mereka juga mulai memanfaatkan limbah menjadi pupuk kompos dan diharapkan dapat berkelanjutan sampai memiliki nilai jual dan di saat yang bersamaan juga mengurangi dampak buruk terhadap lingkungan.